Effects of a hospital‐based leisure activities programme on nurses' stress, self‐perceived anxiety and depression: A mixed methods study. (13th October 2021) - Chen, Feifei; Zang, Yuli; Dong, Hong; Wang, Xiaoyun; Bian, Junping; Lin, Xingfeng
Abstract: Aims: To determine the effects of a hospital‐based leisure activities programme on nurses' stress, self‐perceived anxiety and depression. Background: Nursing work in clinical settings is highly stressful and may result in an increase in nurses' turnover rate, which threatens the quality of nursing care and patient safety. Methods: We used a mixed methods design and a three‐month intervention (January to April, 2019) involving a convenience sample of 176 nurses working at a Chinese tertiary hospital. We conducted 12 semi‐structured interviews and performed a content analysis. The pre‐ and post‐intervention comparisons of nurses' stress, self‐perceived anxiety and depression were performed using a paired t test. Results: The 3‐month leisure activities programme significantly decreased nurses' job stress ( t  = 3.80, p  < .01), perceived personal stress ( t  = 3.30, p  < .01), self‐perceived anxiety ( t  = 3.76, p  < .01) and depression ( t  = 2.73, p  < .01). The qualitative findings revealed five mechanisms linking leisure activities to subjective well‐being: detachment recovery, autonomy, mastery, meaning and affiliation. Conclusions: A hospital‐based leisure activities programme had a positive effect on job stress, self‐perceived anxiety and depression, thus improving nurses' well‐being. Implications for Nursing Management: A hospital‐based leisure activities programme provides a beneficial strategy for ameliorating nurses' psychosocial issues. Interventions aimed at facilitating or increasing nurses' participation in leisure activities are greatly needed.